Sistem Pakar Deteksi Apendisicitis - Yogi Wiyandra; Firna Yenila (Universitas Putra Indonesia YPTK Padang, 2018)
Appendicicitis is found throughout the world and can affect everyone, both men and women. If inflammation of appendicitis cannot be recognized or treated, appendicitis can rupture, make an inflamed sac outside the intestine and cause pus. As a result, objects from the appendix enter the abdominal cavity, causing serious inflammation. To find out appendicitis they must visit a doctor. With this condition a system is designed that is able to provide solutions to patients or users who experience these conditions. It is built an expert system involving doctors who are experts in their field as experts and adapt information through experts and applied to a system. using the backward chaining method in reading the data when the user or patient is consulting. It is based on a website and can be used on various smartphones, the results of this system can also be used in hardcopy